2007
DOI: 10.1080/15287390600755240
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in MTHFR 677 and 1298, GSTM1 and T1, and Metabolism of Arsenic

Abstract: Methylation is the primary route of metabolism of inorganic arsenic in humans, and previous studies showed that interindividual differences in arsenic methylation may have important impacts on susceptibility to arsenic-induced cancer. To date, the factors that regulate arsenic methylation in humans are mostly unknown. Urinary arsenic methylation patterns and genetic polymorphisms in methylenetetrahydrofolate reductase (MTHFR) and glutathione S-transferase (GST) were investigated in 170 subjects from an arsenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 99 publications
(118 reference statements)
5
52
5
Order By: Relevance
“…2 Correlations between WAs and arsenic methylation capacity index of human Fig. 3 The changes of PMI and SMI for both female and male with arsenic levels in drinking water %iAs and %MMA among females suggest that female metabolism may be influenced by sex steroids, resulting in more efficient arsenic methylation compared to males, in agreement with previous studies [30,43]. Previous investigations revealed that younger individuals had more efficient arsenic methylation [21].…”
Section: Discussionsupporting
confidence: 80%
“…2 Correlations between WAs and arsenic methylation capacity index of human Fig. 3 The changes of PMI and SMI for both female and male with arsenic levels in drinking water %iAs and %MMA among females suggest that female metabolism may be influenced by sex steroids, resulting in more efficient arsenic methylation compared to males, in agreement with previous studies [30,43]. Previous investigations revealed that younger individuals had more efficient arsenic methylation [21].…”
Section: Discussionsupporting
confidence: 80%
“…No relationship was observed in G7395A, T14215C, and G35991A polymorphisms. Steinmaus et al (2007) observed that women with the null genotype of GSTM1 (i.e. no enzyme activity) excreted a significantly higher proportion of arsenic as methylarsonate than women with the active genotype.…”
Section: Genetic Polymorphismsmentioning
confidence: 90%
“…Previous studies found that people with the MTHFR TT genotype or the MS GG genotype had a higher MMA% and a lower DMA% than those with either the MTHFR CC genotype or the MS AA genotype, respectively [22,23]. In addition, Steinmaus et al found that subjects with the MTHFR TT genotype excreted a significantly higher inorganic arsenic percentage (InAs%) and a lower DMA percentage (DMA%) [24].…”
Section: Introductionmentioning
confidence: 97%